Comparison of magneto-optical properties of various excitonic complexes in CdTe and CdSe self-assembled quantum dots. (13th May 2016) - Kobak, J; Smoleński, T; Goryca, M; Rousset, J-G; Pacuski, W; Bogucki, A; Oreszczuk, K; Kossacki, P; Nawrocki, M; Golnik, A; Płachta, J; Wojnar, P; et al.
Abstract: We present a comparative study of two self-assembled quantum dot (QD) systems based on II–VI compounds: CdTe/ZnTe and CdSe/ZnSe. Using magneto-optical techniques we investigated a large population of individual QDs. The systematic photoluminescence studies of emission lines related to the recombination of neutral exciton X, biexciton XX, and singly charged excitons (X +, X − ) allowed us to determine average parameters describing CdTe QDs (CdSe QDs): X–XX transition energy difference 12 meV (24 meV); fine-structure splitting δ 1 = 0.14 meV ( δ 1 = 0.47 meV); g -factor g = 2.12 ( g = 1.71); diamagnetic shift γ = 2.5 μ e V T − 2 ( γ = 1.3 μ e V T − 2 ). We find also statistically significant correlations between various parameters describing internal structure of excitonic complexes.